DEATH PENALTY FOR PERPETRATORS OF CHILD SEXUAL VIOLENCE (CASE STUDY OF DECISION NUMBER 5642 K/PID.SUS/2022) - Nida Hana Vina Salmaniqa; Usman, Abdul Kadir (ZILLZELL MEDIA PRIMA, 2023)
The increasing number of cases of sexual violence against minors has made the government required to make new regulations regarding child protection in order to deter the perpetrators. This study aims to explain the application of the death penalty against perpetrators of sexual violence against children in the perspective of law and legal experts as well as the judge's consideration in deciding the criminal case. The object used in this research is Judge Decision Number 5642 K/PID.SUS/2022 and the law regarding the application of the death penalty against child sex offenders. The type of data used is secondary data obtained from legal literature sources regarding child protection and sexual violence. The method used to analyze this research is normative qualitative research method. The application of the death penalty according to the law does not violate the existing rules but is a punishment that has been regulated in it. Another case with one of the legal experts in the field of human rights who stated that the application of the penalty does not reflect the protection of human rights and overrides the interests of protecting the rights of victims.